Effect of miR-223-3p and miR-328a-3p Knockdown on Allergic Airway Inflammation in Rat Precision-Cut Lung Slices - Joanna Nowakowska; Maria Kachel; Wojciech Langwiński; Kamil Ziarniak; Aleksandra Szczepankiewicz (Cells)
Asthma is a major non-communicable disease whose pathogenesis is still not fully elucidated. One of the asthma research models is precision-cut lung slices (PCLSs), and among the therapeutic options, miRNA molecules are of great interest. The aim of our study was to investigate whether inhibition of miR-223-3p and miR328a-3p affects the inflammatory response in PCLSs derived from a rat with HDM-induced allergic inflammation and a control rat. We generated rat PCLSs and transfected them with miR-223-3p and miR-328a-3p inhibitors. RNA was isolated from PCLSs and analyzed by qPCR. We also examined the proteins in the culture medium using the Magnetic Luminex Assay. The comparison between miRNA-transfected PCLSs and non-transfected controls showed significant differences in the expression of several genes associated with allergic inflammation, including Il-33, Ccl5, Prg2 and Tslp, in both the rat with allergic inflammation and the control rat. In the culture medium, we found no significant differences in protein levels between rat with allergic inflammation and the control. Our study highlighted some important issues: the need to extend the model by including more biological replicates, the need to standardize culture conditions, and the need to consider co-transfection with several miRNA inhibitors when modifying miRNAs expression in the PCLS model.